EKSPLORASI PERTAMBANGAN EMAS TRADISIONAL SECARA ILEGAL DI MENGGAMAT ACEH SELATAN DALAM PERFEKTIF FIQIH MUAMALAH - Salman Salman; Siti Aminah (SYARIAH: Journal of Islamic Law, 2022)
Illegal mining activities are businesses carried out by mining individuals, groups or companies/foundations with different laws that do not have a permit from the government in operation in accordance with applicable laws and regulations. Utilization of mining goods, the State must supervise every activity carried out by the mining industry, both private and state-owned, so that the exploration they carry out does not cause environmental pollution. This research is to find out how the implementation of illegal traditional gold mining exploration practices in Menggamat and to understand the implementation of gold mining practices in terms of the concept of utilization of State assets. This study uses a type of qualitative research with data collection techniques of observation, interviews, documentation. The data analysis technique used is descriptive qualitative. The results of this study, that the community of gold mining workers use illegal land and already know the risks of illegality. The implementation of gold mining practices in Menggamat can be seen from the overall nature of what is being done, the traditional gold mining business being carried out is an illegal gold mining business that does not have a permit from the government and is against sharia. Apart from that, other things also made it illegal to mine gold because the land where they used to mine gold belonged to companies that could not be owned individually and all management was delegated to the government. According to Muamalah's fiqh, there are three types of contracts, namely syirkah amlak, syirkah mudharabah, and ijarah.